The Impact of Fiscal Decentralization on Economic Growth in Indonesia: A Literature Study - Digdowiseiso , Kumba (CV ODIS, 2023)
This research examines the impact of fiscal decentralization on economic growth in Indonesia. The research sample comprises a collection of literature pertaining to the subjects of fiscal decentralization and economic growth in Indonesia, sourced from diverse information outlets. The variables under analysis encompass fiscal decentralization and its impact on economic growth. The methodology employed for data analysis involved the utilization of a qualitative literature review approach. The research findings suggest that fiscal decentralization yields favourable outcomes, including the stimulation of investment, productivity, and regional competitiveness. Additionally, it empowers regions, catalyzes regional economic growth, fosters innovation and competition, and mitigates development disparities among regions. Nevertheless, it is important to acknowledge the adverse consequences that may arise from this approach, including the possibility of exacerbating regional inequalities and the susceptibility to corruption in the administration of local funds. The scholarly literature presents varying perspectives on the influence of fiscal decentralization on economic growth. Consequently, scholars have proposed several strategies to optimize the potential benefits of fiscal decentralization, including enhancing regional fiscal capacity, improving the efficiency of intergovernmental transfers, and implementing rigorous oversight mechanisms to ensure effective local financial management